Derivation of high-resolution orthophoto map from multirotor drone survey for application in infrastructure management - Noor Asiah, Mohamad; Nurhidayah, Azmy; Mohamed Yusof, L.; Wahap, M. S. (IOP Publishing Ltd., 2021)
An orthophoto is a geometrically corrected aerial image that can be used in the same approach as map. It provides various geospatial information and therefore plays an important role in infrastructure management. This paper describes the methodology of an aerial survey using a multirotor drone and the processing of aerial images acquired from the survey to produce an orthophoto map. The survey work was carried out using Zenmuse X4S photogrammetric camera controlled by an autopilot multirotor drone at 200m above the ground. Optimal flight path for the autonomous mission was created and organized using the Map Pilot software. Five ground control points were laid within the survey area and their locations were determined using a real-time kinematic global navigation satellite system. Aerial images acquired from the survey were processed with the Pix4Dmapper photogrammetry software. The photogrammetric processing generated a 6 cm-resolution orthophoto map. The presented work demonstrates the practicality of multirotor drone survey and intelligent image processing for non-professionals in deriving high-resolution orthophoto map for application in infrastructure management.